Oslob Aquarium Complex redefining whale shark tourism in Cebu - Villar, Juliet Marie Theresa M.
The tourism rate of Cebu flourished by the time whale shark sighting was mad to be seen by the public. According to the locals, the whale sharks have been around the area since 1980s but the activity of whale shark watching was only developed into a small tourist attraction early 2000s. It instantly became a hit, drawing thousands of international and local tourists to Oslob daily. However, the tourists needed a more organized flow of activities and itinerary within the day, as the current schedule of whale shark watching is done only during the early half of the day. This calls for a need for a development that will give a more organized flow of activities for the incoming tourists, and at the same time, showcase the richness of the marine biodiversity in Cebu. This development is also aimed to inform people regarding the consequences of the interaction with whale sharks. The whole complex follows the concept of ripple effect. It is aligned with the goal to spread awareness to people regarding Philippine marine biodiversity. The Oslob Aquarium complex is composed of four buildings, namely, the main Aquarium building, Whale Shark Viewing Briefing Center, multi-purpose gallery and the covered gallery housing aquaponics.